2011
DOI: 10.1111/j.1540-8175.2011.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Strain Value in the Assessment of Left Ventricular Function and Prediction of Heart Failure Markers in Aortic Regurgitation

Abstract: LV strain analysis in conjunction with NT-proBNP evaluation is a useful tool in assessing LV function in AR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Strain and strain rate echocardiography are superior to tissue Doppler echocardiography in the evaluation of regional myocardial function because they are not affected by the translation and stretching of neighbouring myocardial segments 16. 2D strain and strain rate echocardiography also can assess different clinical conditions, such as hypertension, obesity, post exercise, Marfan syndrome, healthy children and infants 1518…”
Section: Discussionmentioning
confidence: 99%
“…Strain and strain rate echocardiography are superior to tissue Doppler echocardiography in the evaluation of regional myocardial function because they are not affected by the translation and stretching of neighbouring myocardial segments 16. 2D strain and strain rate echocardiography also can assess different clinical conditions, such as hypertension, obesity, post exercise, Marfan syndrome, healthy children and infants 1518…”
Section: Discussionmentioning
confidence: 99%
“…In 2D STE, prior studies have demonstrated the increased sensitivity in detecting subclinical cardiac involvement in conditions such as diabetes, hypertension, amyloidosis, chemotherapy, athlete's heart, hypertrophic cardiomyopathy, aortic regurgitation, acute coronary ischemia, inducible coronary ischemia, differentiation of transmural from subendocardial infarction, and viable from nonviable myocardium. 10,13 In patients with coronary disease, hypertension, amyloidosis, and cardiomyopathies, there is abnormal longitudinal strain well before twist mechanics are affected. In patients with athlete's heart, longitudinal strain is preserved, enabling differentiation of thick walls from hypertrophic cardiomyopathy in young athletes.…”
Section: Three-dimensional Speckle Tracking Strain Echocardiography: mentioning
confidence: 99%
“…In general, with increasing width of the tracking area higher values of PSS, PSSR, PSI and lower values of PLD and PTD were determined in both cohorts (Figs. [3][4][5]. Thus, global PSS was significantly influenced by the width of the tracking area.…”
Section: Resultsmentioning
confidence: 99%
“…1 Wall-motion analysis and deformation imaging by 2D speckle tracking enables further possibilities for the evaluation of left ventricular systolic function or myocardial function, respectively. 2,3 Using 2D speckle tracking specific grayscale patterns of the myocardium are detected from frame to frame over a distinctive period of time. 2D speckle tracking requires frame rates of 40-80 bps to get a sufficiently high lateral resolution for most accurate tracking of the myocardium.…”
mentioning
confidence: 99%